Comparative Study on Carcass Characteristics of Vanaraja and Srinidhi Chicken Reared under Conventional Management System - Katekhaye, Anita F.; Kumar, M. Shashi; Reddy, K. Kondal; Prakash, Gnana; Krishnaiah , N.; Rao, V. Kesava (Journal of Meat Science, 2016)
The present experiment was conducted to compare growth and carcass characteristics of Vanaraja and Srinidhi chicken. There was significant (p≤0.05) difference between body weights of Vanaraja and Srinidhi at day old (39.48±0.32 Vs 33.88±0.33), 4 weeks (341.87±6.50 Vs 277.93±5.91), 8 weeks (1053.26±20.43 Vs 925.03±19.11), 12 weeks (1591.39±18.11 Vs 1405.73±17.78), 16 weeks (2051.83±79 Vs 1869.87±90), 20 weeks (2271.39±94 Vs 2104.61±84) and 24 weeks (2713.55±196 Vs 2357.16±91 g) of age. Dressing percentage in female birds was significantly (p≤0.05) different among Vanaraja and Srinidhi at 16 (66.34±5.81 Vs 65.52±4.52), 20 (72.13±1.12 Vs 71.62±19) and 24 weeks of age (70.27±1.13 Vs 69.33±0.24). Percent giblet weight was significantly (p≤0.05) different in the two varieties at the age of 16 weeks both in males and females. In addition inedible offals weight also showed significant (p≤0.05) difference in both varieties. The weights of cut-up parts differed significantly (p≤0.05) among Vanaraja and Srinidhi varieties. Srinidhi recorded higher meat to bone ratio than Vanaraja at all ages studied. When compared proximate composition of two varieties, it was observed that there were significant (p≤0.05) difference in moisture, protein, fat, ash and cholesterol content between two varieties within same age group and within same sex. Thus, difference in germplasm significantly affects the growth, carcass characteristics and proximate composition of chicken. In general, Srinidhi chicken, with higher growth rate and comparable carcass characteristics to Vanaraja chicken is the best substitute for poultry production.
Keywords: Srinidhi; Backyard chicken; Cut-up-parts; Dressing percentage